2004
DOI: 10.1016/j.cardiores.2004.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Gene dose-dependent atrial arrhythmias, heart block, and brady-cardiomyopathy in mice overexpressing A3 adenosine receptors

Abstract: Objective-An increased expression of adenosine receptors is a promising target for gene therapy aimed at protecting the myocardium against ischemic damage, but may alter cardiac electrophysiology. We therefore studied the effects of heart-directed overexpression of A 3 adenosine receptors (A 3 ARs) at different gene doses on sinus and atrio-ventricular (AV) nodal function in mice.Methods and results-Mice with heart-specific overexpression of A 3 AR at high ( ) or low ( ) levels and their wild-type littermates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…In a similar way, in isolated work-performing hearts, isoproterenol increased the phosphorylation of PLB at Ser 16 (and Thr 17 ) in TG and WT mice. However, 5-HT enhanced the phosphorylation of PLB at Ser 16 (and Thr 17 ) only in perfused hearts from TG mice but not from WT mice (Fig. 4A).…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…In a similar way, in isolated work-performing hearts, isoproterenol increased the phosphorylation of PLB at Ser 16 (and Thr 17 ) in TG and WT mice. However, 5-HT enhanced the phosphorylation of PLB at Ser 16 (and Thr 17 ) only in perfused hearts from TG mice but not from WT mice (Fig. 4A).…”
Section: Resultsmentioning
confidence: 64%
“…The ratios (TG/WT) of the mean expression levels were as follows: SERCA, 1.13; CSQ, 1.05; TRD, 1.03; JCN, 0.90; and PLB, 0.94 (n ϭ 3-6). The phosphorylation state of PLB at Ser 16 was enhanced by isoproterenol in cardiomyocytes from both TG and WT mice (Fig. 3A).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Selective A3R activation is cardioprotective in wildtype hearts and hearts over-expressing A1R, although A3R gene deletion generates an ischaemia-tolerant phenotype [529]. In a later study, it was shown that improved resistance of the heart to ischaemic damage can be achieved by increasing the expression of A3R, without detrimental side effects on heart rate or systolic function [530]. Reduced A3R transcription may contribute to improved ischaemia tolerance in aged hearts [531].…”
Section: Ischaemiamentioning
confidence: 99%